(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate sexual function among postmenopausal women in Da Nang city and to identify factors associated with sexual function. Subjects and methods: A cross-sectional descriptive study was conducted among 850 naturally postmenopausal women who were interviewed and clinically examined at 17 health stations across 17 wards/communes in Da Nang city from August to October 2023. Data were collected through face-to-face interviews using the 14-item CSFQ, which was designed to assess sexual function in postmenopausal women and explore related factors. Results and conclusions: Normal sexual function was observed in 4.4% of participants, while decreased sexual function accounted for 95.6%. No cases of high sexual function were recorded. Sexual function was significantly associated with current occupation, duration of menopause, hot flashes, nocturia, musculoskeletal symptoms, vaginal narrowing, and vaginal dryness.